Understanding Customer Churn in Fixed-Mobile Convergence Services and Mitigation Strategies: Insights from Customer Service Representatives in an Indonesian Telco Company - Reinaldi, Andre Zachary (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Customer churn has become a critical challenge for telecommunication companies, especially with the emergence of Fixed Mobile Convergence (FMC), where mobile services and fiber optic services operate under one ecosystem. Unlike mobile-only services, which rely on fast and seamless fulfillment with minimal field intervention, fiber optic services require extensive physical installation activities involving technicians, equipment, and site readiness. This operational disparity creates new complexities, including data integrity issues, inconsistent customer information across multiple touchpoints, and the need for greater trust in field workforce performance. As customer expectations continue to rise in highly competitive markets such as Indonesia, ineffective churn management not only reduces revenue but also increases acquisition costs and weakens long-term customer value. This study aims to identify the key drivers of churn and propose mitigation strategies based on insights from customer service representatives (CSR), who serve as the primary line of defence in handling customer complaints, deactivations, and terminations. Using a qualitative case study approach, in-depth interviews were conducted and analyzed through thematic analysis, focusing on pricing schemes, service quality, and service usage. The findings indicate that service usage—particularly bill shock—and service quality issues stemming from repeated complaints and stuck orders are the main churn drivers. Meanwhile, pricing is no longer a dominant factor due to existing mitigation programs that adjust prices to match competitors. The study offers practical strategies to reduce churn, including improving transparency, enhancing fulfillment reliability, and aligning key performance indicators to support the effective implementation of these measures.